2012
DOI: 10.2169/internalmedicine.51.7364
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lemierre's Syndrome in Association with Liver Abscess without Any Other Metastatic Lesions

Abstract: Lemierre's syndrome (LS) is characterized by pharyngitis followed by septicemia, internal jugular vein thrombophlebitis, and metastatic embolization in general. LS is commonly caused by Fusobacterium necrophorum. Herein, we present a case of LS with liver abscesses that presented as a sole metastatic lesion. We were not able to diagnose LS until Fusobacterium necrophorum was isolated due to the lack of the common involvement. Doripenem was effective against the pathologic features including the liver abscesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A few (n=2) patients suffered from side effects (hemorrhage or disseminated intravascular coagulation) and were treated accordingly without serious adverse effects. 32 , 87 In the review by Riordan and also previous reviews, the frequency of patients treated with anticoagulants was 21%–23%. The high prevalence in this study might be due to the widespread, unconfirmed hypothesis regarding the positive effects of anticoagulants, which seem to have gained a favorable position in the clinic.…”
Section: Managementmentioning
confidence: 89%
See 1 more Smart Citation
“…A few (n=2) patients suffered from side effects (hemorrhage or disseminated intravascular coagulation) and were treated accordingly without serious adverse effects. 32 , 87 In the review by Riordan and also previous reviews, the frequency of patients treated with anticoagulants was 21%–23%. The high prevalence in this study might be due to the widespread, unconfirmed hypothesis regarding the positive effects of anticoagulants, which seem to have gained a favorable position in the clinic.…”
Section: Managementmentioning
confidence: 89%
“…A larger proportion of cases (71 cases) had septic emboli in the lungs, but septic emboli were also seen in other organs, such as the liver, 12 , 38 , 87 spleen, 81 joints, 38 , 70 heart, 38 and the central nervous system, 29 , 31 even though in smaller numbers.…”
Section: Diagnosismentioning
confidence: 99%
“…Iwasaki et al . [ 4 ] reviewed 13 cases of LS complicated by liver abscesses. Patients were generally young, with a mean age of 21.7 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution must be exercised when selecting antibiotics for the treatment of LS, as Fusobacterium necrophorum exhibits resistance as high as 22% to 60% against penicillin and macrolides [ 5 ]. Iwasaki et al reported treating a case of LS accompanied by a liver abscess with a single agent (carbapenem) [ 4 ]. In addition, antibiotic administration treatment periods of various lengths have been reported across cases, with a range of 2 to 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacterium are usually found as part of the normal oral, gastrointestinal and genital flora, but may induce septic thrombophlebitis in the neighboring neck vessels when the infection is associated with an oropharyngeal abscess. The clinical spectrum may be wide, including abscess formation, bacteremia, puerperal infections, and septic shock[ 2 , 3 , 4 , 5 , 6 ]. Some reliable studies on Fusobacterium [ 7 , 8 ] revealed an overall incidence of bacteremia of 0.55 cases per 100,000 population per year, and a wide spectrum of clinical features.…”
Section: Introductionmentioning
confidence: 99%